PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON-PERFORMING LOAN (NPL), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON EQUITY (ROE) (STUDI KASUS PADA PERBANKKAN DI INDONESIA YANG TERDAFTAR DI BEI TAHUN 2020-2024) - Rabbani, Muhammad Yusuf Rafi; Imronudin, Imronudin (JURNAL LENTERA BISNIS, 2026)
An assessment of the banking sector cannot be separated from its financial condition, as this reflects a company’s ability to generate profits. This study aims to analyze the impact of CAR, NPL, and LDR on ROE for banks listed on the IDX during the 2020–2024 period. This study employs a quantitative approach using secondary data derived from the financial statements of banks listed on the IDX during the 2020–2024 period. The sample was selected using purposive sampling. Data analysis includes descriptive statistics, classical assumption tests, and multiple linear regression with hypothesis testing using the R² test, F-test, and t-test. The results of this study indicate that CAR and NPL have a significant impact on ROE. LDR does not have a significant impact on ROE.